I want to prove that the exterior derivative of a 2-form in $\mathbb{R}^n$: $${\alpha = \sum a_{ij} dx_i \wedge dx_j}$$ is: $${d \alpha = \sum (\frac{\partial a_{ij}}{\partial x_k} + \frac{\partial a_{jk}}{\partial x_i} - \frac{\partial a_{ik}}{\partial x_j})dx_i \wedge dx_j \wedge dx_k.}$$ The thing is that I'm stucked after taking the differential of the function $a_{ij}$ and then multiplying the $dx_k$ term from the 1-form that comes out from ${da_{ij} = \sum \frac{\partial a_{ij}}{\partial x_k}dx_k}$. The answer seems very pleasant (permutating the indices $i,j,k$), but I missed the simple algebraic step that takes to it.

  • $\begingroup$ Use $$dx^i \wedge dx^j = - dx^j \wedge dx^i$$ $\endgroup$ – jimbo Jan 18 '15 at 21:21

I think the explanation comes from what is hidden, namely the range of the summation indices. Because of the anticommutativity $$ \alpha=\sum_{i<j}a_{ij}\,dx^i\wedge dx^j. $$ When you take the exterior derivative it comes out as (I switch temporarily to indices $r,s,t$ - bear with me for a moment) $$ \begin{aligned} d\alpha&=\sum_{r<s}(da_{rs})\,dx^r\wedge dx^s\\ &=\sum_{r<s}\left(\sum_t\frac{\partial a_{rs}}{\partial x^t}\,dx^t\right)\,dx^r\wedge dx^s\\ &=\sum_{r<s}\sum_t\frac{\partial a_{rs}}{\partial x^t}\,dx^t\wedge dx^r\wedge dx^s. \end{aligned} $$ At this point the problem is to list the various ways that we get a term $dx^i\wedge dx^j\wedge dx^k$ with $i<j<k$ to emerge here. We know that $r$ and $s$ are in correct order, but $t$ can be anything. This leaves us with three alternatives:

  • $t=i$, $r=j$, $s=k$, this happens when $t<r<s$
  • $r=i$, $t=j$, $s=k$, this happens when $r<t<s$
  • $r=i$, $s=j$, $t=k$, this happens when $r<s<t$

The anticommutativity rule introduces, respectively, $0$, $1$ or $2$ sign changes, as we need to move $dx^t$ to its correct place. So in the second case we also get a minus sign. The terms coming from $t=r$ or $t=s$ obviously vanish.

This accounts for the three partial derivatives in your sum together with the correct signs. In the end we get, listing the terms in order described above, $$ d\alpha=\sum_{i<j<k}\left(\frac{\partial a_{jk}}{\partial x^i}-\frac{\partial a_{ik}}{\partial x^j}+\frac{\partial a_{ij}}{\partial x^k}\right)\,dx^i\wedge dx^j\wedge dx^k. $$

  • $\begingroup$ Thanks, my real trouble was in turning the sum in $k$ inside the brackets in a sum only in crescent indices. Your explanation was very helpful. $\endgroup$ – B. Chinaski Jan 19 '15 at 2:32

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.